Mapping Patterns Achievement Based on CRISP-DM and Self Organizing Maps (SOM) Methods - Santi Ika Murpratiwi; A.A Ngurah Narendra; Made Sudarma (International Journal of Engineering and Emerging Technology, 2017)
Successful of regional development is a reflection of the good government policy. Many programs created by the local government every period but many programs stop without results. Therefore, we need to evaluation its government programs. Evaluation of government programs must do to prevent the failure of the programs. One way to evaluate the government programs is to collect the support data to see the data model and analyzed the data. In this research will conduct an evaluation on the achievement of RPJMD performance of Bali Province by using data mining. The process of data mining used the CRISP-DM method and Self Organizing Maps (SOM) for mapping the achievement patterns. The used data is RPJMD data in the 2013-2018 period. but the data used for data mining process only 3 years data that is 2014-2016 as a middle evaluation. That data clustered into five clusters. The final result of this research are 78% of assessment indicators in the RPJMD program are inconsistent position and 22% are in an inconsistent position. Moreover, there are 84 assessment indicators that have no reached the target. From that results of data, assessment mapping can use as the guidance of Bali Province to catch up the achievement of RPJMD programs and prepare the next strategies to support the success of the RPJMD program during the RPJMD period.